2023
DOI: 10.1002/cam4.6109
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of high‐risk HPV other than type 16/18 in high‐grade cervical neoplasia among cytology‐negative women: A multicenter retrospective study

Abstract: Background: Human papillomavirus (HPV) is a necessary cause of cervical cancer, and a tool more sensitive than cytology for the early screening of cervical precancers. The two most carcinogenic genotypes HPV 16/18 have been reported in the majority of studies. High-risk HPVs other than HPV 16/18 (non-16/18-hrHPVs) cause approximately a quarter of cervical cancers, and we aimed to analyze the genotype-specific prevalence, risk and diagnostic efficiency of non-16/18-hrHPVs in cervical carcinogenesis among Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In their study of colposcopies of 752 patients over 30 years of age in Turkey with negative cytology and HR-HPV infection other than 16 or 18 , they found pre-invasive lesions, especially in women with genotypes 31 , 33 and 39 so they suggest that patients with these genotypes should be evaluated by colposcopy even if they have negative cytology. Bai et al [ 28 ] reached similar conclusions based on their study of 3,091 patients with normal cytology and HPV infection in China. They found that infections with HPV genotypes 31 , 33 , 35 , 52 , and 58 are significant risk factors for cervical lesions and that patients with multiple infections with HPV 31 , 33 , and 52 should be included in colposcopy screening since the benefit of prevention may outweigh the disadvantages of increased colposcopy in medical services.…”
Section: Discussionmentioning
confidence: 58%
“…In their study of colposcopies of 752 patients over 30 years of age in Turkey with negative cytology and HR-HPV infection other than 16 or 18 , they found pre-invasive lesions, especially in women with genotypes 31 , 33 and 39 so they suggest that patients with these genotypes should be evaluated by colposcopy even if they have negative cytology. Bai et al [ 28 ] reached similar conclusions based on their study of 3,091 patients with normal cytology and HPV infection in China. They found that infections with HPV genotypes 31 , 33 , 35 , 52 , and 58 are significant risk factors for cervical lesions and that patients with multiple infections with HPV 31 , 33 , and 52 should be included in colposcopy screening since the benefit of prevention may outweigh the disadvantages of increased colposcopy in medical services.…”
Section: Discussionmentioning
confidence: 58%
“… 22 , 23 Tumors are defined as vegetations that generate space‐occupying lumpy protrusions in patients due to sudden loss of normal regulation of cells in the body due to various carcinogenic factors. 24 , 25 , 26 Most patients with malignant tumors have bad living habits such as smoking, alcoholism, eating high energy and high fat, or malignant tumors in their tissues caused by exogenous factors such as external environmental stimuli, or malignant tumors in their local tissues caused by endogenous factors such as genetic factors, congenital or acquired immunodeficiency, and endocrine disorders. 27 The clinical manifestations of patients with malignant tumors are mainly divided into local and systemic manifestations.…”
Section: Discussionmentioning
confidence: 99%